Understanding the effects of fabrication process on BaZr0.9Y0.1O3−δ grain-boundary chemistry using atom probe tomography. Issue 15 (23rd March 2023) - Clark, Daniel R.; Diercks, David R.; Ricote, Sandrine; Tauer Dearden, Tania; Sullivan, Neal P.; Medlin, J. Will; Gorman, Brian P.; O'Hayre, Ryan P.
Abstract : We investigate how four different processing routes influence the grain boundary chemistry of the proton-conducting oxide BaZr0.9 Y0.1 O3− δ (BZY10) via atom probe tomography (APT). Differing processing routes can cause large variations in GB chemistry. Abstract : Proton-conducting oxides, such as BaZr0.9 Y0.1 O3− δ (BZY10), are receiving significant scientific attention for application in a variety of electrochemical applications. It has been shown that the synthesis route has a significant effect on the ionic behavior of these materials, especially the grain boundaries (GB). In this study, laser-pulsed atom probe tomography (APT) is used to characterize the GB chemistry of BZY10 samples prepared by four different methods: (1) spark plasma sintering (SPS), (2) conventional sintering followed by high-temperature annealing (HT), (3) conventional sintering with NiO used as a sintering aid (SSR-Ni), and (4) solid-state reactive sintering of oxide precursor powders with NiO as a reactive sintering aid (SSRS-Ni). Oxygen depletion (corresponding to oxygen vacancy accumulation) was observed at every GB in this study, consistent with the positive space-charge GB region commonly assigned to these materials. In contrast to the consistent trends associated with oxygen depletion, cation constituents showed varying segregation/depletion behaviors. The samples that used NiO revealed Ni preferentially segregating to the GB. The most common impurities in BZY10 are Al, Fe, Mg, Si, and Sr, all of which generally accumulate at GBs. In order to quantify these chemical trends, the APT method was optimized for this material supplemented with understanding from density functional theory (DFT). This APT study reveals the complexity of BZY10 GB chemistry and shows that even adjacent GBs in the same material can sometimes show surprisingly different GB chemistry.